Antigen-induced B cell apoptosis is independent of complement C4 - Faust, K B (Blackwell Science Inc, 2007)
Deficiencies in early complement components are associated with the development of systemic lupus erythematosus (SLE) and therefore early complement components have been proposed to influence B lymphocyte activation and tolerance induction. A defect in apoptosis is a potential mechanism for breaking of peripheral B cell tolerance, and we hypothesized that the lack of the early complement component C4 could initiate autoimmunity through a defect in peripheral B lymphocyte apoptosis. Previous studies have shown that injection of a high dose of soluble antigen, during an established primary immune response, induces massive apoptotic death in germinal centre B cells. Here, we tested if the antigen-induced apoptosis within germinal centres is influenced by early complement components by comparing complement C4-deficient mice with C57BL/6 wild-type mice. We demonstrate that after the application of a high dose of soluble antigen in wild-type mice, antibody levels declined temporarily but were restored almost completely after a week. However, after antigen-induced apoptosis, B cell memory was severely limited. Interestingly, no difference was observed between wild-type and complement C4-deficient animals in the number of apoptotic cells, restoration of antibody levels and memory response.